2015
DOI: 10.1118/1.4931605
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Motion‐perturbation method applied to dosimetry of dynamic MLC target tracking—A proof‐of‐concept

Abstract: Based on current results and prior benchmarks of VMS accuracy, the authors postulate that this approach should be applicable to any MLC-tracking treatments where leaf speeds do not exceed those of the current Varian accelerators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Various research groups and vendors are currently working on external MLC control systems that will allow segment by segment control of MLC positions based on the patient's current breathing phase as well as segment by segment dose accumulation algorithyms. 23,[31][32][33][34][35] Typical adult breathing rates are 12-18 breaths per minute. 36 Fast et al have found Elekta agility MLC segment changing lag times on the order of 37-69 ms.…”
Section: Discussionmentioning
confidence: 99%
“…Various research groups and vendors are currently working on external MLC control systems that will allow segment by segment control of MLC positions based on the patient's current breathing phase as well as segment by segment dose accumulation algorithyms. 23,[31][32][33][34][35] Typical adult breathing rates are 12-18 breaths per minute. 36 Fast et al have found Elekta agility MLC segment changing lag times on the order of 37-69 ms.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing this method in dosimetry audits could provide an estimate of volumetric, time-resolved dose errors in planned dose distributions and thus more clinically relevant information. Virtual motion simulation methods have also been developed for the purpose of dynamic MLC-tracking verification using a commercial bi-planar dosimeter, where time-resolved measurements allow identifying transient dose errors during VMAT delivery [68] , [69] , [70] . For dosimetry audits, this approach could be applied to discriminate between errors in the dose delivered to moving targets, which could be due to either target motion or erroneous motion or behaviour of linac parts.…”
Section: Phantom Based Methods For Dosimetry Auditsmentioning
confidence: 99%